Pluronik esaslı enjekte edilebilir hidrojeller - Seçer, Sevgi (Bezmialem Vakıf University, 2020)
From past to the present, important discoveries such as drug discovery, drug administration methods, drug delivery systems and dose adjustment strategies of the drug and their efficiency have been studied and it has been aimed to reach the desired area of drugs, especially in a controlled and targeted manner. Although a number of strategies have been developed in this direction, many studies have experienced problems in compliance with toxicity, biocompatibility and biodegradability criteria. It is aimed to create a variety of methods and systems by using structures (such as polymers, molecules) with very different origins from each other, which have approved certain conditions, for all processes ranging from transporting of a simple drug in the body up to gene therapy. A polymer gel is a network formed by cross-linked polymer chains. This structure consists of two parts, a cross-linked network structure and a liquid part in the network. Characteristic properties of gels are between solid and liquid phase depending on temperature and time scales. Gels are in liquid form at higher temperatures and short time scales. In general, the liquid gels exhibit viscous behavior, while the solid gels exhibit elastic behavior. If the liquid phase is water in the gel network structure, these gels are known as hydrogels. These gels are one of the most important gel systems due to their superior and unique structure. Other main reason for this situation is that they show a high degree of similarity to tissues and organs due to their characteristics. In addition, hydrogel components can be selected and adapted with the desired properties. Especially, pH and temperature sensitive gels are the most preferred hydrogel structures as drug carrier systems due to their adjustable swelling and drug release properties. Block copolymers are important polymer groups used in the formation of hydrogel systems. The most important properties of these polymer solutions are temperature-related micellization and gel formation. Poloxamers, in other words pluronics are in block copolymer class and they are capable of forming a physical cross-linked gel under appropriate conditions which have interactions between hydrofobic and hydrophilic regions and between other pluronic molecules. The pluronic F127 polymer, one of the most well-known species in the pluronic class, is a polymer group found on the basis of the frequently studied hydrogel structures. F127 is approved by U.S. Food and Drug Administration (U.S. FDA). This polymer can be used for many different applicatiob areas such as food additive, cosmetics and pharmaceutical industries. Disadvantages of using F127 hydrogels as biomarkers is limited due to their mechanical weakness and their rapid dissolution in the physiological environment. In order to improve mechanical properties of polymeric materials, many different methods are used such as using of mixed micelle structures, increasing interactions with different polymer chains, addition of nanoparticles to gel system or to create interpenetrating polymer networks (IPN). In this study, F127 based, biocompatible, physically cross-linked, muco-adhesive and injectable, being a gel at body temperature, and most importantly mechanical strength-enhanced gel systems are aimed to be created. In this respect, four different systems were studied by adding hyaluronic acid, cyclodextrins and derivatives, gelatin and poly(lactic-co-glycolic acid) (PLGA) / polyethylene glycol (PEG) structures to the F127 solutions, respectively. The flow behaviors, injectability and muco-adhesive properties of gel structures were examined in details at variable concentrations for each formulation. In next stages, it is planned to use F127 hydrogels in ear surgical operations.
Thesis (Master)--Bezmialem Vakıf University, Biotechnology Master Program, Istanbul, 2019
Keywords: Biyoteknoloji = Biotechnology; Polimer Bilim ve Teknolojisi = Polymer Science and Technology; Hidrojeller = Hydrogels; Mukoadhesifler = Mucoadhesives; Pluronik = Pluronic; Polimer jel = Polymer gel